Intervensi negara terhadap agama : studi konvergensi atas politik aliran keagamaan dan reposisi peradilan agama di Indonesia - Hamidi, Jazim, 1966-; Abadi, M. Husnu, 1950- (Yogyakarta : UII Press, 2001)
On implementation of Indonesian laws and regulations in relationship with religions and state from Islamic viewpoin
Includes bibliographical references (p. 245-258) and index
Keywords: Law -- Indonesia; Islamic law -- Indonesia; Religion and state -- Indonesia